What Is the Practical Utility of Value Research for Organisational Practitioners in a Global Context?. Issue 2 (21st April 2019) - Fischer, Ronald
Abstract : The lead article by Arieli and colleagues provides an overview of value research in broadly defined organisational contexts. The proposed aim of the review is to "integrate theories and empirical studies aiming to portray the role of personal values in shaping the choices and behavior in work settings" (p. 1). In my review I highlight problems with implicit assumptions and limitations of the current literature, in particular: (1) the assumption that values show a universal structure across populations and situations; (2) the assumption that values are relatively stable over a person's career; (3) the unclear ontological status of values combined with a lack of studies examining causality underlying value‐behaviour correlations; (4) the relative effect sizes of value research and their organisational relevance; and (5) unclear paths for actions that organisations may take based on the current value literature (what interventions can organisations adopt to improve value profiles?). In summary, the review provides a summary of current organisational value research that highlights how much we still have to understand about value processes.